2022
DOI: 10.1021/acscatal.2c03847
|View full text |Cite
|
Sign up to set email alerts
|

Linear Regression Model for Predicting Allyl Alcohol C–O Bond Activity under Palladium Catalysis

Abstract: C−O bond activation assisted by activators such as Brønsted acids greatly improves the value of allyl alcohol in allylation; thus, understanding and predicting the activation energy barrier is of paramount importance. Herein, we reveal that multiple linear regression (MLR) analysis is a suitable tool for unifying and correlating different activators and ligands of Pd-catalyzed C−O bond activation of allyl alcohols. We obtain a simple model predicting activation energy barriers with different activators and lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…A plausible mechanism is proposed (Scheme 6) on the basis of the results of the control experiments and the literature. 53–55 The Lewis acid (BF 3 ·ether) first reacts with the basic sulfonamide (NH 2 SO 2 Me) to generate a Lewis acid-sulfonamide pair that further reacts with Cu( i ) to give the copper-Lewis acid-sulfonamide complex ( A ). This key intermediate A coordinates with the cinnamyl cation generated from the dehydration of cinnamyl alcohol, forming the π-allyl-copper intermediate B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible mechanism is proposed (Scheme 6) on the basis of the results of the control experiments and the literature. 53–55 The Lewis acid (BF 3 ·ether) first reacts with the basic sulfonamide (NH 2 SO 2 Me) to generate a Lewis acid-sulfonamide pair that further reacts with Cu( i ) to give the copper-Lewis acid-sulfonamide complex ( A ). This key intermediate A coordinates with the cinnamyl cation generated from the dehydration of cinnamyl alcohol, forming the π-allyl-copper intermediate B .…”
Section: Resultsmentioning
confidence: 99%
“…A plausible mechanism is proposed (Scheme 6) on the basis of the results of the control experiments and the literature. [53][54][55] The Lewis acid (BF 3 •ether) first reacts with the basic sulfonamide (NH 2 SO 2 Me) to generate a Lewis acid-sulfonamide pair that further reacts with Cu(I) to give the copper-Scheme 4 Gram-scale synthesis of 4ad. Lewis acid-sulfonamide complex (A).…”
Section: Resultsmentioning
confidence: 99%
“…A recent example by Yu, Fu, and co-workers showcases this approach to study the activating effect of Brønsted acids on the Pd-catalyzed C−O bond cleavage of allyl alcohols. 54 They created a computationally derived reaction database containing 393 DFT calculated activation barriers, followed by multivariate linear regression (MLR) model training using calculated molecular descriptors. The prediction accuracy was confirmed by a small experimental test set (taken from the literature 55 ), with good agreement between predicted ΔG ‡ and the experimental product yield.…”
Section: Approachesmentioning
confidence: 99%
“…In a related study, Fu and Yu systematically investigated the elementary step of Pd‐catalysed C−OH bond activation of allyl alcohols, using Brønsted acids and phosphines as activators and ligands. Potential activation modes were examined and are shown in Figure 27 [84] . The relevant calculation level is PBE0‐D3/ma‐TZVP/SMD(THF)//PBE0‐D3/def2‐SVP.…”
Section: Transition Metal‐catalysed C−o Activationmentioning
confidence: 99%
“…Potential activation modes were examined and are shown in Figure 27. [84] The relevant calculation level is PBE0-D3/ ma-TZVP/SMD(THF)//PBE0-D3/def2-SVP. Different from the findings in Figure 26, Fu et al found that S N 2 -type oxidative addition is more favorable during CÀ O bond cleavage (TS27 vs TS25 and TS28 vs TS26), and the CÀ O activation in the presence of two molecules of activators is more feasible than the one activator mode (TS27 vs TS28).…”
Section: Pd-catalysed Cà O Activationmentioning
confidence: 99%